Par14 interacts with the androgen receptor, augmenting both its transcriptional activity and prostate cancer proliferation. (30th December 2022) - Naito, Miki; Ikeda, Kenichiro; Aoyama, Shunya; Kanamoto, Mayu; Akasaka, Yasuyuki; Kido, Yuri; Nakanishi, Mikako; Kanna, Machi; Yamamotoya, Takeshi; Matsubara, Akio; Hinata, Nobuyuki; Asano, Tomoichiro; et al.
Abstract: Background: Prostate cancer (PCa) is a major cause of cancer morbidity and mortality for men globally, and androgen signaling clearly drives its onset and progression. Androgen receptor (AR) regulation is complex and remains elusive, despite several studies tackling these issues. Therefore, elucidating the mechanism(s) underlying AR regulation is a potentially promising approach to suppressing PCa. Methods: We report that Par14, one isoform of the prolyl isomerases homologous to Pin1, is a critical regulator of AR transcriptional activity and is essential for PCa cell growth. Results: Par14 was shown to be overexpressed in PCa, based on analyses of deposited data. Importantly, overexpression of Par14 significantly enhanced androgen‐sensitive LNCap cell growth. In contrast, silencing of Par14 dramatically decreased cell growth in LNCap cells by causing cell cycle arrest. Mechanistically, silencing of the Par14 gene dramatically induced cyclin‐dependent kinase inhibitor p21 at both the mRNA and the protein level through modulating the localization of p53. In addition, suppression of Par14 in LNCap cells was shown to downregulate the expressions of androgen response genes, at both the mRNA and the protein level, induced by dihydrotestosterone. Par14 was shown to directly associate with AR in nuclei via its DNA‐binding domain and augment AR transcriptional activity. Conclusion: Thus, Par14 plays a critical role in PCa progression, and its enhancing effects on AR signaling are likely to be involved in the underlying molecular mechanisms. These findings suggest Par14 to be a promising therapeutic target for PCa. Abstract : Prolyl isomerase Par14 directly associates with the androgen receptor. Par14 is mandatory for cell proliferation and its transcriptional activity.